Acceptorless dehydrogenation of alcohols using Cu–Fe catalysts prepared from Cu–Fe layered double hydroxides as precursors. Issue 12 (6th June 2018) - Putro, Wahyu S.; Kojima, Takashi; Hara, Takayoshi; Ichikuni, Nobuyuki; Shimazu, Shogo
Abstract : Cu–Fe catalysts prepared from Cu–Fe layered double hydroxides (LDHs) exhibited high activity for dehydrogenation of alcohols under oxidant- and base-free conditions. Abstract : Catalytically active and stable catalysts are highly desirable for the acceptorless dehydrogenation (AD) of alcohols. Herein, we developed Cu–Fe catalysts prepared from Cu–Fe layered double hydroxide (LDH) precursors. These Cu–Fe catalysts exhibited outstanding activity and selectivity for the AD of various alcohols under oxidant- and base-free conditions and can be steadily reused for up to 5 consecutive runs with no loss of activity.